(untitled) (Zeitschrift für Migrationsforschung, 2024)
Drawing on critical perspectives on archival practices, this article discusses archival practices of migration in the German-speaking world. It focuses on a case study of a family that migrated from Turkey to West Germany as »guest workers« in the 1970s, with their materials now archived at DOMiD. The article explores how personal, familial, and social class backgrounds influence the production, archiving, and accessibility of communication materials. By juxtaposing and analyzing various data materials, such as audio recordings, written correspondence, and a biographical-narrative interview with the donor of materials, the article aims to uncover the richness and complexities of migration in general and the case of »suitcase children« in particular through a critical archival lens. This approach also facilitates a discussion of representation from the practices of collecting and archiving. Migration und soziale Klasse im Archiv: Eine Fallstudie zur Audio- und Schriftkorrespondenz im DOMiD Ausgehend von kritischen Perspektiven auf Archivierung diskutiert dieser Beitrag archivarische Praktiken der Migration im deutschsprachigen Raum. Der Beitrag konzentriert sich auf die Fallstudie einer Familie, die in den 1970er Jahren als »Gastarbeiter« aus der Türkei nach Deutschland migrierte und deren Materialien im DOMiD archiviert werden. Der Beitrag untersucht, wie persönliche, familiäre und soziale Hintergründe die Produktion, Archivierung und Zugänglichkeit von Kommunikationsmaterialien beeinflussen. Durch die Gegenüberstellung und Analyse verschiedener Daten wie Tonaufnahmen, schriftlicher Korrespondenz und einem biografisch-narrativen Interview mit einem Familienmitglied soll der Beitrag den Reichtum und die Komplexität von Migration durch eine kritische Archivperspektive aufzeigen und die Frage von Repräsentation auch aus der Sicht der Sammlung und Archivierung von relevantem Material diskutieren.